Physical-chemical characterization of freeze-dried mango 'Rosa' pulps - Oliveira, Marcela Nobre; Figueirêdo, Rossana Maria Feitosa de; Queiroz, Alexandre José de Melo; Diógenes, Adelino de Melo Guimarães; Sousa, Alison Bruno Borges de; Vasconcelos, Ubieli Alves Araújo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The objective of this study was to perform the physico-chemical characterization of 'Rosa powder' mango pulp obtained by lyophilization. Integral pulp and a formulation containing 30% maltodextrin (drying agent) were used. Samples were homogenized and frozen at -18 ° C for further lyophilization for a period of 72 hours. Analyzes of the pulps (integral and formulated) and the post-obtained were performed for unit parameter, water activity, total soluble solids, pH, total titratable acidity, ascorbic acid and instrumental color. It was verified that the addition of the road agent altered as characteristics of the pulp with decrease of the unit, water activity, titratable total acid and ascorbic acid, increasing the total soluble solids content. In the formulated pulp a 34% increase of the total soluble solids was observed, whereas the reduction of the water activity was almost 80%. In relation to the powder, the maltodextrin product presented a reduction in moisture contents, water activity and titratable total acidity when compared to whole fruit powder. As for color, there was an increase in luminosity (L *), from 72.45 to 78.85 and a decrease in the intensity of yellow (b *), from 62.72 to 35.33, of the formulated powder when compared to the powder without addition of coadjuvant. It was possible to verify that the inclusion of maltodextrin altered the physical-chemical paramedics studied, both in the pulps and lyophilized powder, being the parameter of a unit, water activity and luminosity of the most affected.